A Comprehensive Phenotype of Non-motor Impairments and Distribution of Alpha-Synuclein Deposition in Parkinsonism-Induced Mice by a Combination Injection of MPTP and Probenecid - Han, Na-Ra; Kim, Yu-Kang; Ahn, Sora; Hwang, Tae-Yeon; Lee, Hyejung; Park, Hi-Joon (Frontiers in Aging Neuroscience, 2021)
Parkinson’s disease (PD) is characterized by non-motor symptoms as well as motor deficits. The non-motor symptoms rarely appear individually and occur simultaneously with motor deficits or independently. However, a comprehensive research on the non-motor symptoms using an experimental model of PD remains poorly understood. The aim of the current study is to establish a chronic mouse model of PD mimicking the comprehensive non-motor symptoms of human PD by injection of MPTP and probenecid (MPTP/p). The non-motor and motor symptoms were evaluated by performing buried food, short-term olfactory memory, hot plate, open field, tail suspension, Y maze, novel object recognition, bead expulsion, one-h stool collection, rotarod, rearing, catalepsy and akinesia tests after 10 injections of MPTP/p into mice. The expression levels of α-synuclein, glial fibrillary acidic protein (GFAP), tyrosine hydroxylase (TH) or DJ-1 were analyzed by Western blotting or immunostaining. MPTP/p-treated mice achieved to reproduce the key features of non-motor symptoms including olfactory deficit, thermal hyperalgesia, anxiety, depression, cognitive decline and gastrointestinal dysfunction in addition to motor deficits. The MPTP/p-treated mice also showed the high levels of α-synuclein and low levels of TH and DJ-1 in striatum, substantia nigra, olfactory bulb, hippocampus, amygdala, prefrontal cortex, locus coeruleus or colon. In addition, the expression levels of phosphorylated-α-synuclein and GFAP were elevated in the striatum and substantia nigra in the MPTP/p-treated mice. Taken together, our study clarifies that the chronic MPTP/p-treated mice have a variety of non-motor dysfunctions as well as motor abnormalities by α-synuclein overexpression and dopaminergic depletion. Therefore, the study of comprehensive phenotypes of non-motor symptoms in one PD model would advance in-depth understandings of neuropathological alternations and contribute to future strategies for PD treatment.